(3TQM RHOI GdCUhds - (3eMeO GdLhGO GdcGXei LhGO Hf SYO Hf LhGOs; (3HgGA GdOjf eMeO Hf MSjf GdMGQKj GdgeOGfj GdTjYj GdYGedj,J (B1031 (3g` s ((3eMeO Hf WGgQ GdSeGhi s)
(3ChdgG (B:s
(3hHYO ajbhd abjQ QMeI Hg GdZfi eMeO GdeTJgQ HGdLhGO GdcGXei s
(3BNQgG (B:s
(3aeG cGf Cbhi ai Xfg jLH YdjgG GdYed Hg s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B102s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis